Implementation of the Student Wellbeing Program and Its Implications for Improving Student Learning Motivation - Mistria Harmonis; Faridatul Mukarromah (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This article aims to describe and critically analyze the implementation of the Student Wellbeing Program and its implications for improving students’ learning motivation at Madrasah Aliyah Miftahul Hasanah, Pakuniran, Probolinggo. Methodology: The study employed a qualitative research approach with a case study design and was conducted from September to December 2025. The research participants included the principal, vice principal for curriculum, subject teachers, guidance and counseling (BP/BK) teachers, administrative staff, and Grade XI students of Madrasah Aliyah Miftahul Hasanah. Informants were selected using a snowball sampling technique. Data were collected through in-depth interviews, participant observation, and document analysis, while data analysis followed the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through credibility, dependability, confirmability, and transferability techniques. Main Findings: The findings indicate that the implementation of the Student Wellbeing Program contributes significantly to improving students’ learning motivation through the habituation of religious activities as a means of strengthening self-regulation, controlled technology management that fosters a conducive learning climate, and responsive, humanistic counseling services. Furthermore, the program’s implications include increased student participation and learning engagement, improved discipline and learning focus, and reduced stress levels accompanied by enhanced learning readiness. Novelty/Originality of this study: The novelty of this study lies in framing the Student Wellbeing Program as a systemic, school-level educational intervention integrated with program evaluation. The study examines coherence among objectives, implementation mechanisms, and motivational outcomes, positioning wellbeing as a pedagogical and policy-oriented construct. This education evaluation-informed approach demonstrates how structured wellbeing initiatives operate as accountable, sustainable programs that strengthen students’ intrinsic learning motivation.